ANALISA KEBUTUHAN DAYA LISTRIK DAN BAHAN BAKAR PADA OPERASIONAL MV. MIKO NATALIA KARIMUN DENGAN METODE ANALISA BEBAN - Eko Gustiawan (JURNAL JALASENA, 2021)
MV. Miko Natalia. Karimun is one of the operational vessels owned by PT. Miko Natalia, which in its operational activities requires a lot of materials to meet the ship's electrical power needs. Fuel is one component that might be misused in terms of ship reporting. To reduce suspicion in ship reporting, it is necessary to know the costs incurred by the ship in certain conditions. To find out the amount of the ship's electrical power in each condition, it is necessary to calculate the total power of the ship's equipment using the load analysis method. Based on the calculations that have been done, the MV. Miko Natalia when in a dead condition needs 606.7 kw of power, for sailing conditions it needs 401.21 kw of power, at anchoring conditions it requires 366.95 kw of power and the condition of docking / loading and unloading requires 566.12 kw of power. Meanwhile, the maximum power of the Auxiliary Engine (A / E) that the Miko Natalia Indonesia ship can produce is 450 kw.